RBM39 Alters Phosphorylation of c-Jun and Binds to Viral RNA to Promote PRRSV Proliferation - Song, Yinna; Guo, Yanyu; Li, Xiaoyang; Sun, Ruiqi; Zhu, Min; Shi, Jingxuan; Tan, Zheng; Zhang, Lilin; Huang, Jinhai (Frontiers in Immunology, 2021)
As transcriptional co-activator of AP-1/Jun, estrogen receptors and NF-κB, nuclear protein RBM39 also involves precursor mRNA (pre-mRNA) splicing. Porcine reproductive and respiratory syndrome virus (PRRSV) causes sow reproductive disorders and piglet respiratory diseases, which resulted in serious economic losses worldwide. In this study, the up-regulated expression of RBM39 and down-regulated of inflammatory cytokines (IFN-β, TNFα, NF-κB, IL-1β, IL-6) were determined in PRRSV-infected 3D4/21 cells, and accompanied with the PRRSV proliferation. The roles of RBM39 altering phosphorylation of c-Jun to inhibit the AP-1 pathway to promote PRRSV proliferation were further verified. In addition, the nucleocytoplasmic translocation of RBM39 and c-Jun from the nucleus to cytoplasm was enhanced in PRRSV-infected cells. The three RRM domain of RBM39 are crucial to support the proliferation of PRRSV. Several PRRSV RNA (nsp4, nsp5, nsp7, nsp10-12, M and N) binding with RBM39 were determined, which may also contribute to the PRRSV proliferation. Our results revealed a complex mechanism of RBM39 by altering c-Jun phosphorylation and nucleocytoplasmic translocation, and regulating binding of RBM39 with viral RNA to prompt PRRSV proliferation. The results provide new viewpoints to understand the immune escape mechanism of PRRSV infection.